2016
DOI: 10.1002/ceat.201500317
|View full text |Cite
|
Sign up to set email alerts
|

Oligomerization of n‐Butenes in a Two‐Phase Reaction System with Homogeneous Ni/Al‐Catalysts

Abstract: The oligomerization of n-butenes in a two-phase catalyst system consisting of a Lewis acidic ionic liquid (IL) and a nonpolar phase is described. A highly active catalyst system with NiCl 2 (PMe 3 ) 2 was investigated, resulting in 91 % dimers with N-methylpyrrole as a buffer. The reaction was found to be dependent on the molar ratio of the IL to the catalyst. Additionally, the influence of the Lewis acid was investigated and AlCl 3 was determined as the most suitable for activating the nickel complex. The con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The oligomerization of 1-butene in N -methylpyrrole-buffered ionic liquid ([BMI]­[Cl]/AlCl 3 /NMP) was later studied in more details. , Systematic investigations of IL/NMP/Ni­(PMe 3 ) 2 Cl 2 ratios demonstrated that NMP and IL concentrations are critical parameters. The molar ratio of the IL to N -methylpyrrole needs to be balanced at 1/10, since a high buffer concentration leads to catalyst blockage, whereas a low buffer concentration promotes the formation of higher oligomers.…”
Section: Approaches For Supporting Ni Molecular Oligomerization Catal...mentioning
confidence: 99%
See 1 more Smart Citation
“…The oligomerization of 1-butene in N -methylpyrrole-buffered ionic liquid ([BMI]­[Cl]/AlCl 3 /NMP) was later studied in more details. , Systematic investigations of IL/NMP/Ni­(PMe 3 ) 2 Cl 2 ratios demonstrated that NMP and IL concentrations are critical parameters. The molar ratio of the IL to N -methylpyrrole needs to be balanced at 1/10, since a high buffer concentration leads to catalyst blockage, whereas a low buffer concentration promotes the formation of higher oligomers.…”
Section: Approaches For Supporting Ni Molecular Oligomerization Catal...mentioning
confidence: 99%
“…Both activities and selectivities of homogeneous (PCy 3 ) 2 NiCl 2 -catalyzed propylene dimerization reactions with buffered AlCl 3 co-catalysts (Al/Ni=850, seem to correlate with this analysis. Catalyst precursor used for propylene dimerization in triphenylbismuth buffered Lewis acidic chloroaluminate ionic liquids The oligomerization of 1-butene in N-methylpyrrole-buffered ionic liquid ([BMI][Cl]/AlCl 3 /NMP) was later studied in more details 177,178. Systematic investigations of IL/NMP/Ni(PMe 3 ) 2 Cl 2 ratios demonstrated that NMP and IL concentrations are critical parameters.…”
mentioning
confidence: 99%
“…The results obtained previously indicate that the addition of pure N ‐methylpyrrole leads to a decrease in catalyst activity due to a blockage of the nickel center 13. The addition of pure aluminum trichloride increased the oligomerization yield but resulted in decreased dimer selectivity.…”
Section: Resultsmentioning
confidence: 91%
“…In a previous paper 13, the authors investigated the oligomerization of n ‐butenes in a two‐phase system containing an IL as the solvent for the catalyst and a non‐polar phase as the solvent for the products. The goal was to identify a stable, recyclable catalyst system with high octene (C 8 ) selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the use of available and amortized refinery units (mainly fluid catalytic cracking, FCC, and hydroprocessing units) could contribute to intensify high-quality fuel production from these non-biodegradable wastes (Waste Refinery) [5,30]. FCC units and catalysts have shown an outstanding versatility to treat non-alternative feedstock, usually blended with vacuum gas oil (VGO) [31,32], such as, secondary refinery streams (naphtha, waxes, residues) [33][34][35][36][37], biomass-derived feeds (bio-oil, pyrolysis oil, vegetable oils and animal fats) [38][39][40][41][42][43][44][45][46][47], and plastic wastes [35,48,49]. The possibility of upgrading STPO alone and/or blended with VGO has been reported by several authors [29,50,51].…”
Section: Introductionmentioning
confidence: 99%